INCREASING STUDENTS’ ACTIVITY AND KNOWLEDGE LEVEL USING TEST ASSIGNMENTS - Makhmudov, Zokirjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article examines the possibilities of improving the knowledge level of students in higher education institutions using test tasks.